2014
DOI: 10.1186/1297-9716-45-26
|View full text |Cite
|
Sign up to set email alerts
|

Early infections by myxoma virus of young rabbits (Oryctolagus cuniculus) protected by maternal antibodies activate their immune system and enhance herd immunity in wild populations

Abstract: The role of maternal antibodies is to protect newborns against acute early infection by pathogens. This can be achieved either by preventing any infection or by allowing attenuated infections associated with activation of the immune system, the two strategies being based on different cost/benefit ratios. We carried out an epidemiological survey of myxomatosis, which is a highly lethal infectious disease, in two distant wild populations of rabbits to describe the epidemiological pattern of the disease. Detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…This proves that the animals were partially protected from mother antibodies during infection. Having in mind the conclusions made by Fenner and Marshall (10) and Joubert et al (12) that young rabbits are extremely sensitive to myxomatosis strains with different virulence, the observations published by Marchandeau et al (13) confirmed that mother antibodies cannot totally protect from infection, but soften the manifestation of disease and do not interfere with immune answer. The same authors proved the circulation of IgG antibodies that are also of mother origin.…”
Section: Role Of Antibodies In Myxomatosismentioning
confidence: 90%
“…This proves that the animals were partially protected from mother antibodies during infection. Having in mind the conclusions made by Fenner and Marshall (10) and Joubert et al (12) that young rabbits are extremely sensitive to myxomatosis strains with different virulence, the observations published by Marchandeau et al (13) confirmed that mother antibodies cannot totally protect from infection, but soften the manifestation of disease and do not interfere with immune answer. The same authors proved the circulation of IgG antibodies that are also of mother origin.…”
Section: Role Of Antibodies In Myxomatosismentioning
confidence: 90%
“…infections in which host individuals that survive infection become resistant against re-infection), recurrent patterns are primarily driven by the availability of susceptible juveniles [13][14][15][16]. Whereby, the time between birth and susceptibility can be delayed by natural immunity or maternally acquired antibodies [17][18][19]. The re-introduction rate of pathogens is assumed to be crucial for perpetuating immunizing diseases [20].…”
Section: Introductionmentioning
confidence: 99%
“…they do not die when exposed to the virus) and may or may not support virus replication-this period of insusceptibility lasts for approximately three weeks [21]. Disease survival results in antibodies that are passed by the mothers as maternal antibodies to the embryo, further attenuating infections and disease early in the life of juveniles [17][18][19]. In contrast to RHD, juveniles infected with MYXV have a lower chance of survival than infected adults [27].…”
Section: Introductionmentioning
confidence: 99%
“…The European rabbit is one of the most used laboratory animal models for immunologic research, including the study of atherosclerosis, 19 intestinal immunity, 20 arthritis, 21 cancer, 22 Alzheimer’s disease 23 and several viral infections. 24 26 In addition, the European rabbit is a key species in the Mediterranean ecosystem, where it is strongly affected by two viral diseases, rabbit hemorrhagic disease (RHD) and myxomatosis. 27 32 RHD is caused by a single-stranded RNA virus, the rabbit hemorrhagic disease virus (RHDV), while myxomatosis is caused by the myxoma virus (MYXV), a double-stranded DNA virus.…”
Section: Introductionmentioning
confidence: 99%